Phenolic compounds from peel and callus extracts of sweet lime (Citrus medica) - Kaur, Ramandeep; Manchanda, Pooja; Sidhu, Gurupkar S (The Indian Journal of Agricultural Sciences, 2020)
An experiment was conducted to quantify and evaluate bioactivity of phenolics from peel and callus extracts of sweet lime (Citrus medica). Cotyledon, epicotyl and hypocotyl-derived calli of sweet lime were obtained on solid MS medium supplemented with 2, 4-D and Kin. Cotyledon exhibited the best response on callus induction medium. Various extracts were prepared from peel and callus using different solvents, i.e. 50, 80 and 90% (v/v) of ethyl acetate, isopropyl alcohol, methanol and ethanol, employing maceration, orbital shaking, ultrasonic assisted and soxhlet extractions followed by estimation of total phenolic content (TPC) and total flavonoid content (TFC). Soxhlet extraction with 80% ethanol from peel was found to be the best combination as the yields of extracts; TPC and TFC were found to be the highest. Peel extract of sweet lime (80% ethanol, soxhlet) showed the highest antioxidant potential, i.e. 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay and antibacterial potential against Bacillus aryabhattai and Klebsiella sp. Thus, peel of sweet lime, being a potential source of phenolic compounds with antioxidant and antimicrobial properties, may be used as an ingredient for the preparation of functional foods.